2016
DOI: 10.1007/s00210-016-1225-7
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin efficiency assessment in non-tumor (HB4a) and tumor (MCF-7) human breast cells

Abstract: The search for anticancer drugs has led researchers to study salinomycin, an ionophore antibiotic that selectively destroys cancer stem cells. In this study, salinomycin was assessed in two human cell lines, a breast adenocarcinoma (MCF-7) and a non-tumor breast cell line (HB4a), to verify its selective action against tumor cells. Real-time assessment of cell proliferation showed that HB4a cells are more resistant to salinomycin than MCF-7 tumor cell line, and these data were confirmed in a cytotoxicity assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This pathway controls G1/S phase transition. Sal induces cell cycle arrest [53]. Fourteen out of 26 (54%) of the genes associated with the pathway were modulated by the drug, with 12 of them being downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway controls G1/S phase transition. Sal induces cell cycle arrest [53]. Fourteen out of 26 (54%) of the genes associated with the pathway were modulated by the drug, with 12 of them being downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Salinomycin induced cell-cycle arrest and decreased expression of anti-apoptotic genes in MCF-7 cells, thereby causing apoptotic cell death of tumor cells, whereas non-tumor cells were able to evade this toxic effect. 86…”
Section: Salinomycin As An Anticancer Agentmentioning
confidence: 99%
“…Salinomycin induced cell-cycle arrest and decreased expression of anti-apoptotic genes in MCF-7 cells, thereby causing apoptotic cell death of tumor cells, whereas non-tumor cells were able to evade this toxic effect. 86 Salinomycin induced apoptosis in human T-cells of leukemia, but Fuchs et al 2 reported that normal human T-lymphocytes were not harmed. Salinomycin is more potent in inhibiting P-gp than verapamil, which is a known drug for inhibiting ABC transporter.…”
Section: Advantage Of Salinomycin Over Other Anticancer Agentsmentioning
confidence: 99%
“…Despite the predominant antitumor effects and fewer adverse effects of Sal, the mechanism by which Sal brings about cancer cell death while non-malignant cells are exempted from the lethal effects remaining poorly understood. According to the studies both in vivo and in vitro, such following mechanisms that mitochondria-dependent cell death [ 20 , 21 ], Death receptor - mediated cell death [ 14 ], increased DNA damage and cell cycle arrest [ 22 , 23 ], p-glycoprotein inhibition [ 24 , 25 ] have been reported to involve the predominant anticancer effects of Sal. However, those mechanisms may just play a partial role in the anti-cancer effects of Sal as conventional chemotherapeutical agents rely on them to induce cancer cell death.…”
Section: Introductionmentioning
confidence: 99%